Healthy Eating: Understanding the Nutrition Facts Label - Karla P. Shelnutt (EDIS)
FCS8883, a 2-page illustrated fact sheet by Karla P. Shelnutt, explains the nutrition facts label — why it is needed and how to read it. Published by the UF Department of Family Youth and Community Sciences, October 2009.